2022
DOI: 10.3889/oamjms.2022.9963
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice Regarding Needle Stick Injuries Among Health Care Workers in Baghdad Teaching Hospital and Ghazy Al-Hariri Hospital for Surgical Specialties in 2020

Abstract: Background: Needle stick injuries are serious occupational hazards in the transmission of a variety of bloodborne diseases, more than twenty pathogens can be transmitted through NSI including hepatitis B virus, hepatitis C virus, and human immunodeficiency virus (AIDS) among healthcare workers. Objectives: Assess the knowledge, attitude and practice of health care workers towards needle stick injuries. Determine the prevalence of needle stick injuries among healthcare workers and its predisposing factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…This study reported that the 208 nurses working in the public hospital, Malaysia had high levels of knowledge, high levels of practice, and a positive attitude. This study backs up what the previous study found: nurses are better HCWs than other HCWs in terms of their KAP (Al-Khalidi & Nasir, 2022;Yunihastuti et al, 2020). The study indicated NSI case experience was lower (5.3%), compared to 34.5% in northeast Ethiopia (Berhan et al, 2021) and 33.3% in Jordan (Yunihastuti et al, 2020).…”
Section: Socio-demographicsupporting
confidence: 78%
“…This study reported that the 208 nurses working in the public hospital, Malaysia had high levels of knowledge, high levels of practice, and a positive attitude. This study backs up what the previous study found: nurses are better HCWs than other HCWs in terms of their KAP (Al-Khalidi & Nasir, 2022;Yunihastuti et al, 2020). The study indicated NSI case experience was lower (5.3%), compared to 34.5% in northeast Ethiopia (Berhan et al, 2021) and 33.3% in Jordan (Yunihastuti et al, 2020).…”
Section: Socio-demographicsupporting
confidence: 78%